The Collagen-like Protein gp12 Is a Temperature-dependent Reversible Binder of SPP1 Viral Capsids - Zairi, Mohamed (American Society for Biochemistry and Molecular Biology, 2014)
Icosahedral capsids of viruses are lattices of defined geometry and homogeneous size. The (quasi-)equivalent organization of their protein building blocks provides, in numerous systems, the binding sites to assemble arrays of viral polypeptides organized with nanometer precision that protrude from the capsid surface. The capsid of bacterial virus (bacteriophage) SPP1 exposes, at its surface, the 6.6-kDa viral polypeptide gp12 that binds to the center of hexamers of the major capsid protein. Gp12 forms an elongated trimer with collagen-like properties. This is consistent with the fold of eight internal GXY repeats of gp12 to build a stable intersubunit triple helix in a prokaryotic setting. The trimer dissociates and unfolds at near physiological temperatures, as reported for eukaryotic collagen. Its structural organization is reacquired within seconds upon cooling. Interaction with the SPP1 capsid hexamers strongly stabilizes gp12, increasing its T(m) to 54 °C. Above this temperature, gp12 dissociates from its binding sites and unfolds reversibly. Multivalent binding of gp12 trimers to the capsid is highly cooperative. The capsid lattice also provides a platform to assist folding and association of unfolded gp12 polypeptides. The original physicochemical properties of gp12 offer a thermoswitchable system for multivalent binding of the polypeptide to the SPP1 capsid surface.